Theacher´s abilites and attitudes for classroom management - Jara, Eicka; Jaramillo, Bertha
The purpose of this thesis is to identify abilities and attitudes to manage a classroom. Our thesis is based in the abilities and attitudes which must be used by the teachers in a classroom. Our theoretical framework develops the following topics: Teachers Abilities: Importance of abilities in the classroom, Analysis and Selection of Abilities, How to Find Abilities?; Proper Attitudes for Teachers: Attitudes: A Tool or a Weapon, Attitudes for classroom management, Motivating Students through attitudes; Abilities and Attitudes as An Ideal Complement: Abilities and Attitudes in the classroom, and A Teacher?s Model. Therefore, it is necessary to know the correct teachers attitudes into a classroom and some proper abilities to teach better. At first instance, we proposed a profile to improve the teaching-learning process and have good results. In this way, we hope to contribute to the improvement of teachers? educational practice and relationship with their students in some way.